Relationship between Maternal Immunological Response during Pregnancy and Onset of Preeclampsia - Alicia Martínez-Varea; Begoña Pellicer; Alfredo Perales-Marín; Antonio Pellicer (Journal of Immunology Research, 2014)
Maternofetal immune tolerance is essential to maintain pregnancy. The maternal immunological tolerance to the semiallogeneic fetus becomes greater in egg donation pregnancies with unrelated donors as the complete fetal genome is allogeneic to the mother. Instead of being rejected, the allogeneic fetus is tolerated by the pregnant woman in egg donation pregnancies. It has been reported that maternal morbidity during egg donation pregnancies is higher as compared with spontaneous or in vitro fertilization pregnancies. Particularly, egg donation pregnancies are associated with a higher incidence of pregnancy-induced hypertension and placental pathology. Preeclampsia, a pregnancy-specific disease characterized by the development of both hypertension and proteinuria, remains the leading cause of maternal and perinatal mortality and morbidity. The aim of this review is to characterize and relate the maternofetal immunological tolerance phenomenon during pregnancies with a semiallogenic fetus, which are the spontaneously conceived pregnancies and in vitro fertilization pregnancies, and those with an allogeneic fetus or egg donation pregnancies. Maternofetal immune tolerance in uncomplicated pregnancies and pathological pregnancies, such as those with preeclampsia, has also been assessed. Moreover, whether an inadequate maternal immunological response to the allogenic fetus could lead to a higher prevalence of preeclampsia in egg donation pregnancies has been addressed.